Performance of public works department in procurement activity compliance to PPA-2006, & PPR -2008 - Rahman, SK. Toufiqur (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.